Pengaruh Keputusan Investasi terhadap Nilai Perusahaan dengan Struktur Modal sebagai Variabel Intervening pada Perusahaan Food & Beverage yang Terdaftar di BEI - Nadila Rizkiwati; Muhadjir Anwar (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Company value is a certain condition of the company after several years of operation, which is an indicator of public trust in the company. The purpose of the study is to determine whether investment decisions in food and beverage companies listed on the IDX for the 2018-2021 period can affect company value through capital structure as an intervening variable. In this study using quantitative research. For the study, only 24 companies were selected from 32 food and beverage companies. Purposive sampling is the sampling method used in this study. Path Analysis is the method of analysis used. The results of the study show that Investment Decisions contribute to Company Value. Capital Structure is not able to be an intervening variable in the influence of investment decisions on Company Value. Keywords: Investation decision; Capital Structure; The value of the company.